2020
DOI: 10.1111/jfpp.15083
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of peach quality treated with essential oil coatings

Abstract: The effect of edible coatings incorporated with essential oils of cinnamon, basil, and thyme with and without sodium alginate, glycerol, and Tween 80 on the physiochemical, sensory, and shelf life of peach fruit were investigated using the multivariate technique. All coatings retarded the changes in fruit as compared to control samples. Combination of essential oils and alginate were more effective as compared to these chemicals alone. Changes in the physiochemical and sensory attributes were slow at the start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, comparing coated samples, it was evident that the samples coated with PE and PNE had lower scores for odour, since the presence of CEO created an additional aroma not liked by the evaluator. This additional aroma is contributed by the volatile compounds present in EOs, affecting sensory acceptability (Ayub et al ., 2021). In terms of overall visual quality and overall acceptance, apple treated with PNE presented the highest score followed by PE, whereas that for uncoated was lowest.…”
Section: Resultsmentioning
confidence: 99%
“…However, comparing coated samples, it was evident that the samples coated with PE and PNE had lower scores for odour, since the presence of CEO created an additional aroma not liked by the evaluator. This additional aroma is contributed by the volatile compounds present in EOs, affecting sensory acceptability (Ayub et al ., 2021). In terms of overall visual quality and overall acceptance, apple treated with PNE presented the highest score followed by PE, whereas that for uncoated was lowest.…”
Section: Resultsmentioning
confidence: 99%
“…In the second step, for producing specific combinations of PG and CEO solutions, various contents of CEO (0%, 0.25%, 0.5%, and 0.75% (v/v)) were added to the PG solutions from the first step. These treatments were selected according to our previous study and also other scientific reports (Ayub et al., 2020; Barzegar et al., 2018; Wang et al., 2021). Next, the solutions were fully emulsified by a homogenizer (WTW‐Disper) at 12,000 rpm for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Alginate–apple puree edible coating containing 0.1% oregano oil significantly reduced the consumer preference for fresh‐cut apples throughout the 14‐day storage at 4°C (Rojas‐Grau et al., 2007). However, a recent study showed that edible coatings containing cinnamon, basil, or thyme oil better maintained the sensory characteristics (color, aroma, taste, and appearance) of whole peaches compared to uncoated fruits (Ayub et al., 2020). Incorporation of 7.3–36.1 g/L cinnamon leaf oil in pectin edible coating increased the odor acceptability of fresh‐cut peaches; the acceptance increased in proportion to essential oil concentrations (Ayala‐Zavala et al., 2013).…”
Section: Edible Coatingmentioning
confidence: 99%